2023
DOI: 10.1038/s41598-023-28089-y
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic resonance imaging based radiomics model to predict mitosis cycles in intracranial meningioma

Abstract: The aim of this study was to develop a magnetic resonance imaging (MRI) based radiomics model to predict mitosis cycles in intracranial meningioma grading prior to surgery. Preoperative contrast-enhanced T1-weighted (T1CE) cerebral MRI data of 167 meningioma patients between 2015 and 2020 were obtained, preprocessed and segmented using the 3D Slicer software and the PyRadiomics plugin. In total 145 radiomics features of the T1CE MRI images were computed. The criterion on the basis of which the feature selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…For example, Ari et al showed that radiomic-based machine learning can be used to non-invasively predict pseudoprogression in high-grade gliomas [2]. Krähling et al developed an MRI-based radiomics model to predict mitotic cycles in intracranial meningiomas before surgery [3]. In Musigmann et al, it was shown that ML algorithms can predict possible total and subtotal resections of skull meningiomas using pre-treatment T1 post-contrast MR images [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ari et al showed that radiomic-based machine learning can be used to non-invasively predict pseudoprogression in high-grade gliomas [2]. Krähling et al developed an MRI-based radiomics model to predict mitotic cycles in intracranial meningiomas before surgery [3]. In Musigmann et al, it was shown that ML algorithms can predict possible total and subtotal resections of skull meningiomas using pre-treatment T1 post-contrast MR images [4].…”
Section: Introductionmentioning
confidence: 99%